A new liquid–liquid microextraction method by ultrasound assisted salting-out for determination of triazole pesticides in water samples coupled by gas chromatography-mass spectrometry. Issue 3 (7th February 2015) - Xu, Xin-Yi; Ye, Jing-qing; Nie, Jing; Li, Zu-Guang; Lee, Maw-Rong
<x xml:space="preserve">Abstract</x> A simple, fast and green method termed "ultrasound assisted salting-out homogeneous liquid–liquid microextraction (UASO-HLLME)" has been developed and validated for the quantitative determination of triazole pesticides in water.